2019
DOI: 10.1016/j.ajhg.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes

Abstract: SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomalrecessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Because organs, cell types, and gene functions are well conserved across vertebrates, analysis of zebrafish mutants provides insights into gene functions in other vertebrates, including humans [ 58 , 59 ]. Zebrafish are used widely to validate candidate human disease genes and elucidate the molecular mechanisms and pathophysiology of disease [ 27 , 28 , 33 , 60 62 ] as well as for drug discovery [ 63 ].…”
Section: Benefits Of Each Model Organism In the Moscmentioning
confidence: 99%
“…Because organs, cell types, and gene functions are well conserved across vertebrates, analysis of zebrafish mutants provides insights into gene functions in other vertebrates, including humans [ 58 , 59 ]. Zebrafish are used widely to validate candidate human disease genes and elucidate the molecular mechanisms and pathophysiology of disease [ 27 , 28 , 33 , 60 62 ] as well as for drug discovery [ 63 ].…”
Section: Benefits Of Each Model Organism In the Moscmentioning
confidence: 99%
“…The phenotypes shown by genetically affected zebrafish resemble the symptoms found in human patients. Whereas gene expression studies are insufficient for a sensible model ( dymeclin ; Denais et al, 2011 ), the study of the hypomorph extl3 mutant boxer ( Volpi et al, 2017 ), the morpholino downregulation of ddrgk1 ( Egunsola et al, 2017 ) or nasna ( van Karnebeek et al, 2016 ), and the CRISPR/Cas9 editing of tonsl ( Burrage et al, 2019 ) could be considered appropriate zebrafish models for these four SE(M)D dysplasias ( Supplementary Table 1 ). Although these models do not exactly reproduce the symptoms found in humans, several molecular and cellular results support their great potential.…”
Section: Zebrafish Models For Human Skeletal Diseasesmentioning
confidence: 99%
“…Moreover, the facial dysmorphism found in patients with SEMD with intellectual disorders NANS type could be associated with the small head and craniofacial cartilage phenotypes obtained in zebrafish morphants of nasna gene ( van Karnebeek et al, 2016 ). Finally, several skeletal phenotypes have been described in zebrafish with CRISPR/Cas9-edited tonsl gene that resembles those of SPONASTRIME dysplasia ( Burrage et al, 2019 ). Lethality before 20 days post-fertilization (dpf), accelerated vertebra ossification, short body size, and spinal abnormalities in the mutant resemble the spine abnormalities, disproportionately short stature, and exaggerated lumbar lordosis or scoliosis found in humans with SPONASTRIME dysplasia ( Burrage et al, 2019 ).…”
Section: Zebrafish Models For Human Skeletal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In AGAP1, LRP5, and TONSL, two other rare heterozygous variants were identi ed in different patients. It has been reported that these genes associate with vertebral or Chiari malformations [34][35][36][37][38][39]. The related information is displayed in Table 3.…”
Section: Clinical Features and Radiographic Parameters Of The Cohortmentioning
confidence: 99%